Inflammatory Endotypes and Microbial Associations in Chronic Rhinosinusitis - Hoggard, Michael; Waldvogel-Thurlow, Sharon; Zoing, Melissa; Chang, Kevin; Radcliff, Fiona J.; Wagner Mackenzie, Brett; Biswas, Kristi; Douglas, Richard G.; Taylor, Michael W. (Frontiers in Immunology, 2018)
A complex mix of inflammatory and microbial associations underscores the chronic inflammatory condition chronic rhinosinusitis (CRS), and the etiology remains poorly understood. Recent work has begun to delineate between variants (endotypes) of CRS on the basis of inflammatory biomarkers. This study aimed to assess inflammatory patterns in CRS phenotypes, identify putative endotypes of CRS, and to assess inflammatory associations with the sinonasal microbiota. Ten cytokines and six inflammatory cell types were assessed in mucosal biopsies from 93 CRS subjects and 17 controls via cytometric bead array and immunohistochemical techniques. Putative endotypes were identified via cluster analysis of subjects on the basis of inflammatory markers and comorbidities including polyposis, asthma, and aspirin sensitivity. Finally, previously published bacterial data for this cohort were reanalyzed to evaluate associations with inflammatory markers and CRS subtypes. Inflammatory patterns were highly variable within standard CRS phenotypes. Cluster analysis identified eight subject clusters, with strong delineation on the basis of polyposis and asthma, but also subtle distinctions in inflammatory markers. An association was also identified between depletion of several “health-associated” bacterial taxa, reduced bacterial diversity and increased overall bacterial load, with markers of inflammation and clinical severity. This study contributes to ongoing efforts to define distinct endotypes of CRS on the basis of underlying inflammatory processes, and also offers compelling evidence of a link between bacterial community dysbiosis and inflammation in CRS. Further resolving the heterogeneity of CRS is vital to inform clinical management and personalized treatment approaches.